Uncle Jed's barbershop - Mitchell, Margaree King.; Ransome, James (New York : Simon & Schuster Books for Young Readers, 1993)
Despite serious obstacles and setbacks, Sarah Jean's Uncle Jed, the only black barber in the county, pursues his dream of saving enough money to open his own barbershop.
Wilson's Children, October 2010.
Elem. School Library Collection, June 2000.
School Library Journal, September 1996.
Publisher's Weekly, September 1996.
Booklist, May 1996.
Horn Book, January 1997.
Keywords: Uncles -- Fiction; Barbers -- Fiction; African Americans -- Fiction; Uncles -- Fiction; Barbers -- Fiction; African Americans -- Fiction